The Influence of Prices, Promotions and Supporting Facilities on Consumer Satisfaction at Kosan Keken, Bengkulu City - Rajaliu, Haqil; Wijaya , Ermy; Rahman , Abdul (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2023)
The purpose of this study was to determine the effect of price, promotion, and supporting facilities on consumer satisfaction at the Keken boarding house in Bengkulu City. This research is quantitative descriptive. The method used is a questionnaire. The sample in this study were 80 respondents. Based on the results of multiple linear regression test shows Y = 13,684 + 0, 282 (X1) + 0, 580 (X2) + 0, 602 (X3) + 4,815, namely the regression constant value of 13.684 means that if there is no variable Price (X1) of 0 (none), the value of the promotion variable (X2) is 0 (none), the value of the facility variable (X3) and customer satisfaction (Y) has increased by 13.684. While the results of the t-test of the price variable (X1) show tcount 2.559 > ttable 1.991 and a significance of 0.012 <0.05, then the results of the hypothesis Ha are accepted and Ho is rejected, meaning that the price (X1) has a significant effect on consumer satisfaction (Y), the test results promotion (X2) shows t count 3.016 > t table 1.991 and significance 0.003 < 0.05, then the results of the hypothesis Ha are accepted and Ho is rejected, meaning that promotion (X2) has a significant effect on consumer satisfaction (Y), and the results of the facility test (X3) shows t count 5.247 > t table 1.991 and significance 0.000 < 0.05, then the results of the hypothesis Ha are accepted and Ho is rejected, meaning that the facility (X3) has a significant effect on consumer satisfaction (Y) at the Keken boarding house in Bengkulu City. Based on the comparison of the Fcount value with Ftable, the Fcount value is greater than the Ftable value, namely 14,349 > 2.72, it can be concluded that the hypothesis is accepted, meaning that there is a simultaneous influence between the effect of price (X1), promotion (X2), facilities (X3) on satisfaction consumer (Y). This can be seen at the significance level of 0.000 < 0.05.